SISTEM INFORMASI E-LEARNING UPT SMPN 1 IV JURAI BERBASIS WEB - Mallisza, Danyl; Yahyan, Wahyuni; Nofriwandi, Vindro (JENTIK, 2023)
The learning process at SMPN 1 IV JURAI is still conventional, that the teaching and learning process between students and teachers is only carried out by meetings between students and teachers in the classroom. If the teacher is absent and the learning time is limited by the school, then automatically the learning process will be hampered because it still relies on face-to-face meetings in the classroom. The design of this web-based E-Learning information system at SMPN 1 IV JURAI aims to make it easier for teachers to provide subject matter and exams for students at UPT SMPN 1 IV JURAI. The development of information systems in making this software uses PHP as a script language used to create web pages and MySQL as a database for data storage. This final project produces an e-learning information system that will be able to help and facilitate teachers and students in the teaching and learning process and streamline the teaching and learning process at UPT SMPN 1 IV JURAI. With this online learning class can help the teaching and learning process to be more optimal. Students can easily get subject matter, exams and make it easy to collect assignments and exams and find out the results / grades they get.